Food service management web platform based on XML specification and web services - Sabioni, Pedro (2013)
Company’s importance and competitiveness is no longer just to enable automatic processes but also to fulfill needs of humans as we nowadays also live concerned with enjoyment and pleasure, in order to complement people's lives. Built from the decision to bring to market a fully customized product to the customer comes the Fragus Company. This company enables services of Personal Chef and Bartender aiming to bring convenience in one of life's greatest pleasures: eating. This publication aims at briefly describing a web platform of this company and its usefulness, which is to some extend provided by the use of structured data based on XML and related technologies, for better supporting the Company’s services and to enable an easy way for information storing and processing over the web, namely through web services.